1-2-3 draw cool cartoon stuff : a step-by-step guide - Barr, Steve, 1958- ([Columbus, N.C.] : Peel Productions ; Cincinnati, OH : Distributed to the trade and art markets in North America by North Light Books, 2003)
Provides step-by-step instructions for drawing cartoons.
5.3
3-6
3-6
Keywords: Cartooning -- Technique -- Juvenile literature; Cartooning -- Technique; Drawing -- Technique; Cartooning -- Technique; Drawing -- Technique